Microheater array powder sintering: A novel additive manufacturing process. (January 2018) - Holt, Nicholas; Van Horn, Ausitn; Montazeri, Mahsa; Zhou, Wenchao
Abstract: One of the most versatile additive manufacturing (AM) processes is selective laser sintering (SLS), which scans a powder bed with a laser beam to fuse powder particles layer by layer to build 3D objects for prototypes and end products with a wide range of materials. However, it suffers from slow printing speed due to the pointwise scanning and high energy consumption due to the requirement of a high-power laser. In this paper, we propose a novel method of additive manufacturing which replaces the laser beam with an array of microheaters as an energy source to sinter powder particles. This method, referred to as Microheater Array Powder Sintering (MAPS), has the potential to significantly increase the printing speed by layer-wise sintering and reduce the power consumption due to the lower power requirements of the microheater array. This paper is to provide a proof-of-concept for this proposed new method. First, a thin-film microheater was designed and simulated with an experimentally validated numerical model to demonstrate that it can be used as an alternative energy source to sinter powder particles by reaching a target temperature of 600 °C within milliseconds at a power consumption of 1.2 Watts. The numerical model was used to simulate the MAPS process by placing the heater in close proximity to the powder particles. Simulation results showed that heat can be effectively transferred over an airgap to raise the temperature of the powder particles to their sintering temperature. Different process parameters (e.g., airgap, material properties, time, printing resolution, etc.) are discussed. An experimental MAPS system was then implemented to provide a proof-of-concept with the designed microheater and a custom airgap control apparatus. A straight line was successfully printed on thermal paper using the experimental MAPS system, which suggests the proposed MAPS process is feasible.